An effective control solution for doubly-fed induction generator under harsh balanced and unbalanced voltage sags. (March 2019) - Tilli, Andrea; Conficoni, Christian; Hashemi, Ahmad
Abstract: This paper presents a novel control algorithm for the rotor-side converter of Doubly-Fed Induction Generators. The main goal is to endow the system with effective Low Voltage Ride Through capability, under harsh balanced and unbalanced grid voltage sags, without relying on dedicated auxiliary hardware, which is commonly adopted to sustain severe line faults. In this respect, nonlinear control theory arguments are applied to design a controller capable of mitigating oscillations (particularly on rotor currents and voltages) arising during line faults, therefore preventing the system from disconnecting for protection. The proposed solution adopts both feedforward and feedback terms. The former stems from a thoughtful analysis of the system internal dynamics, taking into account the effects of line voltage perturbations, which is exploited to design feasible state trajectories for the generator electromagnetic variables. Specifically, such references do not contain poorly-damped oscillatory modes of the machine natural dynamics, expressed in synchronously rotating frames (such components turn into slowly varying DC ones in a stationary frames). Then, a state feedback unit is designed according to modern saturated control techniques, accounting for constraints on rotor voltage, and steering real variables toward references, where priority given to rotor currents, to avoid rotor-side converter tripping due to overcurrent. In addition, a non standard line voltage reconstruction and dip detection scheme, based on adaptive state observers, is designed, to reliably cope with challenging faulty conditions. Detailed numerical simulations validate the proposed method benefits under severe symmetric and asymmetric dip scenarios.